Charge separated states of endohedral fullerene LiC20 - Yang, Yi-Fan; Gromov, Evgeniy; Cederbaum, Lorenz S. (The journal of chemical physics, 2019)
We report on high-level coupled-cluster calculations of electronic states of the neutral endohedral fullerene LiC20. All computed states of neutral Li@C20 are found to be the charge separated states of the Li+@C−20C20−<msubsup><mtext>C</mtext>20−</msubsup> type. Using the state-of-the-art EA-EOM-CCSD method, we found that neutral Li@C20 (D3d) possesses several valence and superatomic charge separated states with considerable electron binding energies, the strongest bound state of Li+@C−20C20−<msubsup><mtext>C</mtext>20−</msubsup> being the 12Eu state (6.73 eV). The valence charge separated states correspond to two sets of states of C−20C20−<msubsup><mtext>C</mtext>20−</msubsup>. The states 12Eu, 12A2u, 22Eu, and 22A2u correspond to the respective bound states of C−20C20−<msubsup><mtext>C</mtext>20−</msubsup>, and the states 22A2g, 12Eg, 12A1g, and 42Eu correspond to the unbound states of C−20C20−<msubsup><mtext>C</mtext>20−</msubsup>. There are eight superatomic states with electron binding energy higher than 1.0 eV, being much stronger bound than the single weakly bound superatomic state of the parent fullerene anion. The analysis of the radial density distribution of the excess electron on the carbon cage indicates the important role of the inner part of the superatomic states in forming the charge separated states.